CT experimental study on concrete specimens based on the principle of minimum energy. (May 2015) - Xinyu, L.; Faning, D.; Feng, P.; Hongmei, T.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to study the mesoconcrete crack evolution laws, based on the computed tomography test, studying the input work and the energy consumed during the failure procedure for the pressure and tension conditions; calculating the failure area of the specimen in the CT pictures and analysing the transformation of the input work from outside during the concrete failure procedure. It turns out that concrete failure pattern abides by the minimum energy principle, when the failure energy of specimen increases, its strength increase, the failure area and failure pattern depend on the stress state. Failure surface of concrete sample under static loading move forward with the weak configuration; under dynamic loading, the failure surface is following the energy release of the fastest route forward.